The role of financial elites in banking supervision in Japan from 1927 to 1998 - Eiji Hotori (The European Association for Banking and Financial History (EABH), 2016)
Following the collapse of the bubble economy in Japan, banking supervisors and bank examiners were severely criticized by the media as human capital had long been viewed the key element of Japanese banking supervision. The purpose of this paper is to analyze the bank supervisors career paths over the long term, including "amakudari" appointments from among the Directors of the Financial Inspection Department of the Ministry of Finance, and the Director-Generals of the Bank Examination Department of the Bank of Japan. The paper analyzes the performance of several regional banks that accepted the appointment of an ex-Director or an ex-Director-General as their president in order to examine whether such an amakudari relationship worsened such banks management. The majority of ex-Directors and ex-Director-Generals entered a regional bank or a regional bank II, many of which were already experiencing problems. Regarding the regional banks, lower growth rates of loans were observed in all cases, and lower loan/deposit ratios or higher capital/asset ratios were observed in most. These findings suggest that the link between the amakudari relationship and the bubble economy in the late 1980s was not as straightforwardly negative as is generally considered.
Keywords: N25; N35; N45; 330; financial history; human capital; regional bank